PEMIKIRAN MUHAMMAD NATSIR TENTANG AGAMA DAN NEGARA - Ainul Badri (Pascasarjana IAIN Metro, 2020)
Natsir's view of the relationship between Islam and the state is that religion is not merely a ritual of worship in everyday terms such as prayer or fasting, but religion includes all principles, boundaries in muamalah and social relations. Therefore, in order to ensure that these rules and standards can apply and run as they should, it is necessary and not necessary, there must be strength in social life in the form of power in the state, as warned by the Prophet Muhammad to Muslims that Allah is Allah. holder of the ruling power. It seems that Natsir wants to emphasize that Islam and the state are integrally related, even symbiotic, that is, they are reciprocally related and need each other. In this case, religion needs a state, because with religion and the state it can develop in the field of ethics and morals. This is because in Natsir's understanding that Islam is a complete teaching. Islamic teachings do not contain other aspects such as the field of law regarding statehood, so the establishment of a state is a necessity as argued by H.A.R. Gibb, For Natsir Islam is not just a religion, but also a complete civilization. For that in Islam it is irrelevant to separate Religion from the State because universal Islamic values cannot be separated from the idea of forming a state.